3D High‐Content Culturing and Drug Screening Platform to Study Vascularized Hepatocellular Carcinoma in Hypoxic Condition. Issue 12 (16th August 2021) - Lim, Jungeun; Choi, Hyeri; Ahn, Jungho; Jeon, Noo Li
Abstract : Hypoxia in the tumor microenvironment (TME) is the leading cause of metastasis and chemoresistance in cancer cells. Numerous 3D in vitro models have been proposed to study hypoxic stress, but none have enabled sufficient analysis of hepatocellular carcinoma (HCC). Herein, a 3D in vitro tumor vasculature model for HCC is introduced to investigate cellular responses and drug resistance under hypoxic conditions through high‐content screening. The hypoxic TME of vascularized HCC can be established by maintaining the platform in a hypoxia chamber and is used to analyze the diverse physiological responses of the TME to normoxia, hypoxia, and drug treatment. The proposed platform also demonstrates the hypoxic status naturally induced by 3D HCC spheroids for comparison with single HCC cells cultured in the hypoxia chamber. The results show that hypoxic stress in the HCC vasculature promotes angiogenesis, hypoxia‐inducible factor 1 (HIF‐1) expression, and proliferation; it also enhances drug resistance. The hypoxic tumor vasculature of the model generates cellular responses that are also expressed in the physiological hypoxic microenvironment of HCC. These findings suggest that our high‐content microfluidic platform can be applied as a powerful tool to develop anticancer therapeutics, which have remained elusive because of hypoxia in the TME. Abstract : The low oxygen environment in vivo, hypoxia leads to enhanced tumor progression and drug resistance in cancer cells. This in vitro injection‐molded platform reconstitutes hepatocellular carcinoma under low oxygen conditions and provides insight into the effects of hypoxia. The formation of new blood vessels and cancer cell proliferation as well as increased chemoresistance are highlighted.